Falling stars [large type] - Michaels, Fern (Wheeler Publishing, a part of Gale, a Cengage Company, 2022)
"Emily Ammerman has always felt at home amid the ski runs and slopes of Snowdrift Summit, the Colorado resort her family has operated for decades. Snow is her element, and she doesn't hesitate when a new client asks her to train him to ski The Plunge, one of Colorado's most treacherous runs. But Zach Ryder is no regular client. On screen, he's famous for starring as a daring CIA officer who always saves the day. In real life, he's just as handsome and charming as his alter ego, though not everyone is impressed. Some are concerned about what kind of impact these slick, showbiz types will have on their town. As for Emily--she's got a secret, and it's one she can't reveal to anyone, especially not to Zach: she's his biggest fan. But she's also a professional. She'll train him till he's ready to tackle any slope, but she won't fall in love with him, the way so many others have. Still, not everything in life can be planned, and sometimes, no matter how hard you try, you just can't help but fall..."--